Interferon regulatory factor 4 deficiency in CD8+ T cells abrogates terminal effector differentiation and promotes transplant acceptance. Issue 4 (12th October 2020) - Zou, Dawei; Fu, Jinfei; Guo, Zhiyong; Chen, Wenhao
Summary: Allogeneic CD8 + cytotoxic T cells play an essential role in rejecting transplanted allografts, but how their effector function is regulated on a transcriptional level remains unclear. Herein, we investigate the role of interferon regulatory factor 4 (IRF4) in controlling CD8 + T‐cell function in response to transplant. B6. Rag1 −/− mice were adoptively transferred with CD8 + T cells isolated from either Irf4 fl/fl Cd4 ‐ Cre (T‐cell‐specific Irf4 ‐deficient) or Irf4 fl/fl control mice, followed by BALB/c skin transplantation. Recipients that received Irf4 ‐deficient CD8 + T cells permanently accepted the skin allografts, whereas recipients that received control CD8 + T cells acutely rejected the transplanted skins. Mechanistically, compared with the transferred control CD8 + T cells in B6. Rag1 −/− recipients, the transferred Irf4 ‐deficient CD8 + T cells lost the capacity to differentiate into CD127 − KLRG1 + terminal effector cells, barely produced effector cytokines and cytotoxic molecules (e.g. IL‐2, IFN‐γ, TNF‐α, granzyme A and granzyme B), and displayed defect in proliferative capacity, evident by their decreased Ki67 expression and lower frequencies. Moreover, the transferred Irf4 ‐deficient CD8 + T cells displayed low expression of transcription factors ID2 and T‐bet that govern the terminal effector T‐cell programmes, and high expression of transcription factor TCF1 that maintains the naïve‐memory T‐cell programmes. Hence, IRF4 deficiency in CD8 + T cells abrogates their terminal effector differentiation and promotes transplant acceptance. These findings suggest that targeting IRF4 expression represents an attractive and promising therapeutic approach for inducing transplant acceptance. Abstract : Ablation of IRF4 in CD8+ T cells abrogates their function to reject skin allografts. Mechanistically, IRF4 deletion in CD8+ T cells impairs the production of proinflammatory cytokines and cytotoxic molecules, and completely abolishes their differentiation into terminal effector cells.